K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 4 2019

\(4\frac{3}{7}:\left(\frac{7}{5}.4\frac{3}{7}\right)\)

\(=\frac{31}{7}:\left(\frac{7}{5}.\frac{31}{7}\right)\)

\(=\frac{31}{7}:\frac{31}{5}\)

\(=\frac{5}{7}\)

\(4\frac{3}{7}\div\left(\frac{7}{5}\times4\frac{3}{7}\right)\)

\(=\frac{31}{7}\div\left(\frac{7}{5}\times\frac{31}{7}\right)\)

\(=\frac{31}{7}\div\frac{31}{5}=\frac{31}{7}\times\frac{5}{31}=\frac{5}{7}\)

30 tháng 3 2020

cách này mình tự nghĩ 

\(\hept{\begin{cases}A=\frac{4}{7}+5+\frac{3}{7^2}+\frac{5}{7^3}+\frac{6}{7^4}\\B=\frac{5}{7^4}+5+\frac{6}{7^2}+\frac{4}{7}+\frac{5}{7^3}\end{cases}}\)

\(\Rightarrow A-B=\left(\frac{4}{7}-\frac{4}{7}\right)+\left(\frac{5}{7^3}-\frac{5}{7^3}\right)+\left(5-5\right)+\left(\frac{3}{7^2}-\frac{6}{7^2}\right)+\left(\frac{6}{7^4}-\frac{5}{7^4}\right)\)

\(\Rightarrow A-B=-\frac{3}{7^2}+\frac{1}{7^4}\)

\(\Rightarrow A-B=\frac{-3\times7^2}{7^4}+\frac{1}{7^4}\)

mà \(-3\times7^2< 1\Rightarrow\frac{1}{7^4}>\frac{-3\times7^2}{7^4}\Rightarrow B>A\)

21 tháng 9 2017

\(P=\frac{\frac{3}{7}-\frac{3}{13}+\frac{3}{37}}{\frac{5}{7}-\frac{5}{17}+\frac{5}{37}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{\frac{7}{5}-\frac{7}{4}+\frac{7}{3}-\frac{7}{2}}\)

\(=\frac{3\left(\frac{1}{7}-\frac{1}{13}+\frac{1}{37}\right)}{5\left(\frac{1}{7}-\frac{1}{17}+\frac{1}{37}\right)}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{-7\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}\)

\(=\frac{3}{5}+\frac{1}{-7}\)

\(=\frac{16}{35}\)

17 tháng 9 2015

\(A=\frac{3.\left(\frac{1}{7}-\frac{1}{17}+\frac{1}{37}\right)}{5.\left(\frac{1}{7}-\frac{1}{17}+\frac{1}{37}\right)}+\frac{1.\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}{\left(-7\right).\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}\)

\(A=\frac{3}{5}+\frac{-1}{7}\)

\(A=\frac{21}{35}+\frac{-5}{35}\)

\(A=\frac{16}{35}\)

17 tháng 9 2015

\(A=\frac{\frac{3}{7}-\frac{3}{17}+\frac{3}{37}}{\frac{5}{7}-\frac{5}{17}+\frac{5}{37}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{\frac{7}{5}-\frac{7}{4}+\frac{7}{3}-\frac{7}{2}}\)

\(=\frac{3.\left(\frac{1}{7}-\frac{1}{17}+\frac{1}{37}\right)}{5.\left(\frac{1}{7}-\frac{1}{17}+\frac{1}{37}\right)}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{-\frac{7}{2}+\frac{7}{3}-\frac{7}{4}+\frac{7}{5}}\)

\(=\frac{3}{5}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{-7.\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}\)

=3/5+(1/-7)

=3/5-1/7

=16/35

So sánh:

\(P=\frac{4}{7}+5+\frac{3}{7^2}+\frac{5}{7^3}+\frac{6}{7^4}\)

\(Q=\frac{5}{7^4}+5+\frac{6}{7^2}+\frac{4}{7}+\frac{5}{7^3}\)

Ta có : \(P=\left\{\frac{4}{7}+5+\frac{5}{7^3}\right\}+\left\{\frac{3}{7^2}+\frac{6}{7^4}\right\}\)

           \(Q=\left\{\frac{4}{7}+5+\frac{5}{7^3}\right\}+\left\{\frac{5}{7^4}+\frac{6}{7^2}\right\}\)

So sánh : \(\frac{3}{7^2}+\frac{6}{7^4}\)và \(\frac{5}{7^4}+\frac{6}{7^2}\)

Ta có : \(\frac{3}{7^2}+\frac{6}{7^4}=\frac{49.3}{7^4}+\frac{6}{7^4}\)

            \(\frac{5}{7^4}+\frac{6}{7^2}=\frac{5}{7^4}+\frac{49.6}{7^4}\)

Vì 49.3 + 6 < 49.6 + 5 nên Q > P.

           

5 tháng 7 2016

\(A=\frac{\frac{3}{7}-\frac{3}{17}+\frac{3}{37}}{\frac{5}{7}-\frac{5}{17}+\frac{5}{37}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{\frac{7}{5}-\frac{7}{4}+\frac{7}{3}-\frac{7}{2}}\)

\(=\frac{3\left(\frac{1}{7}-\frac{1}{17}-\frac{1}{37}\right)}{5\left(\frac{1}{7}-\frac{1}{17}-\frac{1}{37}\right)}+\frac{1.\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}{-7\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}\)

\(=\frac{3}{5}+\frac{-1}{7}\)

\(=\frac{21}{35}-\frac{5}{35}\)

\(=\frac{16}{35}\)

5 tháng 7 2016

\(A=\frac{3.\left(\frac{1}{7}-\frac{1}{17}-\frac{1}{37}\right)}{5.\left(\frac{1}{7}-\frac{1}{17}-\frac{1}{37}\right)}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}}{7.\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{4}-\frac{1}{5}\right)}\)

\(A=\frac{3}{5}+\frac{1}{7}=\frac{21}{35}+\frac{5}{35}=\frac{26}{35}\)

29 tháng 10 2023

5và 3/8-1 và 5/6

 

Bài 1:

a) Ta có: \(6\frac{5}{7}-\left(1\frac{3}{4}+2\frac{5}{7}\right)\)

\(=6\frac{5}{7}-1\frac{3}{4}-2\frac{5}{7}\)

\(=4\frac{5}{7}-1\frac{3}{4}\)

\(=\frac{33}{7}-\frac{7}{4}\)

\(=\frac{132}{28}-\frac{49}{28}=\frac{83}{28}\)

b) Ta có: \(7\frac{5}{9}-\left(2\frac{3}{4}+3\frac{5}{9}\right)\)

\(=7\frac{5}{9}-2\frac{3}{4}-3\frac{5}{9}\)

\(=4\frac{5}{9}-2\frac{3}{4}\)

\(=\frac{41}{9}-\frac{11}{4}\)

\(=\frac{164}{36}-\frac{99}{36}=\frac{65}{36}\)

c) Ta có: \(\frac{-3}{5}\cdot\frac{5}{7}+\frac{-3}{5}\cdot\frac{3}{7}+\frac{-3}{5}\cdot\frac{6}{7}\)

\(=\frac{-3}{5}\cdot\left(\frac{5}{7}+\frac{3}{7}+\frac{6}{7}\right)\)

\(=\frac{-3}{5}\cdot2=-\frac{6}{5}\)

d) Ta có: \(\frac{1}{3}\cdot\frac{4}{5}+\frac{1}{3}\cdot\frac{6}{5}-\frac{4}{3}\)

\(=\frac{1}{3}\cdot\frac{4}{5}+\frac{1}{3}\cdot\frac{6}{5}-\frac{1}{3}\cdot4\)

\(=\frac{1}{3}\left(\frac{4}{5}+\frac{6}{5}-4\right)\)

\(=\frac{1}{3}\cdot\left(-2\right)=\frac{-2}{3}\)